Terra incognita of vitality problem: Open issues. Part 2 - Vladimir A. Tolochek (Saratov State University, 2021)
The relevance of studying resilience is among other things conditioned by faster evolution of social objects, increase in general uncertainty, lack of stability, complexity and ambiguity of the dynamics of their state, which, in their turn, lead to an increase in the requirements for adaptation mechanisms of an individual and social groups (families, collectives, sports teams, managerial or project teams); the importance of an individual's socio-psychological and psychological resources is increasing. Not all spontaneously formed adaptation mechanisms of individual and group subjects are developed in a timely manner, correspond to life situations or change optimally in accordance with changes in the purposes and requirements of the environment. The purpose of the study is to investigate human resilience under conditions of uncertainty; the subjects of the study are social and psychological mechanisms and resources of human resilience; the research methods are historical and theoretical analysis and analysis of the empirical research results. The hypothesis is that maintaining resilience of an individual and social groups through the development of prosocial behavior mechanisms according to the specific model (prototype) is the first stage. Subsequent stages of resilience development presuppose formation of adaptation mechanisms initiated and supported by the evolution of the subject's "internal conditions". It is stated that the two states of a person are considered within the boundaries of historically formed paradigms: "below the norm" and "within the norm" of social, psychological and physical functioning. Its characteristics are described by such concepts as "improvement", "positive adaptation", "preservation", "optimal state", etc. Resilience is viewed as the person's achievement and maintenance of "social homeostasis" with an orientation towards pro-social behavior models of others and reproduction of such models. Individual's advancement to a higher level of social functioning and his/her positive professional evolution are often associated with repeated changes and complications of the social conditions of social environment (medium), with the growth in its "resistance"; they remain understudied and retain a kind of "terra incognita" status. One of the possible and probable approaches that contribute to overcoming the binary thinking of the historically established paradigm can be the use of a new methodology, i.e. construction of system triads (that recreate social objects' integrity) and linear triads that restore the sequences of social objects' syntheses when they are integrated into systems of a greater generality.